A Stronger Rhizosphere Impact on the Fungal Communities Compared to the Bacterial Communities in Pecan Plantations - Liu, Junping; Tang, Yujie; Bao, Jiashu; Wang, Hankun; Peng, Fangren; Tan, Pengpeng; Chu, Guolin; Liu, Shuai (Frontiers in Microbiology, 2022)
Understanding microbial communities associated with bulk and rhizosphere soils will benefit the maintenance of forest health and productivity and the sustainable development of forest ecosystems. Based on MiSeq sequencing, we explored the differences between the bulk soil and the rhizosphere soil on bacterial and fungal communities of pecan plantation. Results suggested that rhizosphere-associated fungal rather than bacterial community structures differed from bulk soil, and rhizosphere soil had lower bacterial diversity than bulk soil. Actinobacteria and Cantharellales were the bacterial and fungal biomarkers of the rhizosphere soil of pecan plantation, respectively. The pH, ammonium nitrogen (NH4+-N), nitrate nitrogen (NO3--N) and total carbon (TC) contents drove microbial community structure and composition. Soil bacterial are mainly involved in the N cycle, while soil fungi are mainly involved in the C cycle. The bacterial network was simpler and more stable in the rhizosphere soil than in the bulk soil. However, fungal showed opposite network patter. Overall, in terms of bacterial and fungal communities, the rhizosphere soil behaves more healthily than the bulk soil and has a higher potential for nutrient cycling.